Responsibility to Protect (R2P): Exploringthe Dilemma Between International Intervention and State Sovereignty - Ernawati, Ninin; Sukardi, Dina Haryati; Yatani, Vincent Godana (Faculty of Law Universitas Lampung, 2025)
The Responsibility to Protect (R2P) is an international law principle that affirms the obligation of the international community to protect populations from genocide, crimes against humanity, and other mass atrocities. The Rohingya crisis in Myanmar highlights the persistent tension between R2P and state sovereignty. This article analyzes that tension by examining the challenges of implementing R2P in Myanmar, where the government has consistently rejected foreign intervention. Using a conceptual analysis and a case research of the Rohingya refugee crisis, the research explores how sovereignty claims and regional norms, particularly ASEAN’s principle of non-interference, constrain international responses. The findings show that although R2P provides a normative framework for addressing gross human rights violations, its implementation in Myanmar has been hindered by state resistance and regional political dynamics. This article contributes to debates on international justice and sovereignty by offering insights into the limitations and potential pathways for more effective R2P implementation within the ASEAN context.